2003
DOI: 10.1016/s0006-3495(03)70051-4
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Interactions within Subsites of a Monomeric Enzyme: Kinetics of Fluorogenic Substrates of PI-Specific Phospholipase C

Abstract: Two novel water-soluble fluorescein myo-inositol phosphate (FLIP) substrates, butyl-FLIP and methyl-FLIP, were used to examine the kinetics and subsite interactions of Bacillus cereus phosphatidylinositol-specific phospholipase C. Butyl-FLIP exhibited sigmoidal kinetics when initial rates are plotted versus substrate concentration. The data fit a Hill coefficient of 1.2-1.5, suggesting an allosteric interaction between two sites. Two substrate molecules bind to this enzyme, one at the active site and one at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
3
16
1
1
Order By: Relevance
“…Occupancy of both catalytic and regulatory sites within the overall extended peptide binding site is thus an important determinant for efficient trimming. Similar subsite activation models have been proposed to explain the length preference of bovine RNAse A43, and the sigmoidal velocity plots observed for the monomeric B. subtilis PI-PLC when assayed with short-chain lipid analog substrates44. The location of the regulatory site(s) within the ERAP1 structure is not yet clear in the absence of structural data for a bound peptide complex, but one possible site might be the inner surface of top of helices H20 and H22, which in the closed conformation would contact an extended version of the tripeptide model shown in Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Occupancy of both catalytic and regulatory sites within the overall extended peptide binding site is thus an important determinant for efficient trimming. Similar subsite activation models have been proposed to explain the length preference of bovine RNAse A43, and the sigmoidal velocity plots observed for the monomeric B. subtilis PI-PLC when assayed with short-chain lipid analog substrates44. The location of the regulatory site(s) within the ERAP1 structure is not yet clear in the absence of structural data for a bound peptide complex, but one possible site might be the inner surface of top of helices H20 and H22, which in the closed conformation would contact an extended version of the tripeptide model shown in Fig.…”
Section: Discussionsupporting
confidence: 62%
“…PC surfaces enhance cIP hydrolysis, whereas anionic surfaces inhibit enzyme activity (by acting as competitive inhibitors). Similar effects are also observed for the phosphotransferase activity of PI-PLC using long-chain and shortchain PI (6, 12) as well as monomeric nonlipid substrates (9). It has been documented that several peripheral membrane proteins oligomerize when bound to membranes (e.g.…”
Section: Discussionsupporting
confidence: 55%
“…For the soluble cIP reaction, k cat was increased, and K m decreased in the presence of PC interfaces (4,8). That work suggested that PC binds to an activator site on the bacterial enzyme that is distinct from the enzyme active site, a model confirmed recently using artificial substrates (9). However, the details of the conformational change upon PC binding that leads to improved enzyme efficiency are not known.…”
mentioning
confidence: 85%
“…Enzymes that display a positive cooperativity with a Hill coefficient higher than 1 do not always correspond to an oligomeric structure. It is well established that there is a class of monomeric enzymes that display positive cooperativity for substrate binding (41)(42)(43)(44)(45). This positive cooperativity has been explained by a theoretical "mnemonical" model (43).…”
Section: Figmentioning
confidence: 99%